2008
DOI: 10.1002/ejic.200701043
|View full text |Cite
|
Sign up to set email alerts
|

Oxidoperoxidotungsten(VI) Complexes with Secondary Hydroxamic Acids: Synthesis, Structure and Catalytic Uses in Highly Efficient, Selective and Ecologically Benign Oxidation of Olefins, Alcohols, Sulfides and Amines with H2O2 as a Terminal Oxidant

Abstract: The reaction of a solution of freshly precipitated WO3 in H2O2 separately with the secondary hydroxamic acids N‐benzoyl‐N‐phenylhydroxamic acid (BPHAH), N‐benzoyl‐N‐ortho‐tolylhydroxamic acid (BOTHAH), N‐benzoyl‐N‐meta‐tolylhydroxamic acid (BMTHAH), N‐benzoyl‐N‐para‐tolylhydroxamic acid (BPTHAH) and N‐cinnamyl‐N‐phenylhydroxamic acid (CPHAH) afforded [WO(O2)(BPHA)2] (1), [WO(O2)(BOTHA)2] (2), [WO(O2)(BMTHA)2] (3), [WO(O2)(BPTHA)2] (4) and [WO(O2)(CPHA)2] (5), respectively. Aqueous tungstate solution, on reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…As part of our continued interest in using oxoperoxomolybdenum complexes as oxidation catalysts, we were intrigued by previous reports [26,27] at the failure of the Mo-complexes to activate H 2 O 2 and by using a molybdenum complex, PPh 4 [MoO(O 2 ) 2 (SaloxH)] [6] (SaloxH 2 = Salicylaldoxime) as catalyst along with NaH CO 3 as cocatalyst [28,29] we were able to activate H 2 O 2 and the integrated catalyst, co-catalyst and oxidant functioned as a very efficient peroxidic epoxidation system. Inspired by this result, we reported some other peroxo complexes, which showed higher to much higher catalytic efficiencies [6][7][8][9][10] for olefin epoxidation. In this paper, we report the synthesis, structural characterization, and catalytic epoxidation activities of two oxodiperoxo complexes, [MoO(O 2 ) 2 (PyCOXH) (H 2 O)] (1) (PyCOXH = Pyridine-2-carboxaldoxime) and PMePh 3 [MoO(O 2 ) 2 (PyCO)] (2) (PyCOH = Pyridine-2-carboxylic acid).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…As part of our continued interest in using oxoperoxomolybdenum complexes as oxidation catalysts, we were intrigued by previous reports [26,27] at the failure of the Mo-complexes to activate H 2 O 2 and by using a molybdenum complex, PPh 4 [MoO(O 2 ) 2 (SaloxH)] [6] (SaloxH 2 = Salicylaldoxime) as catalyst along with NaH CO 3 as cocatalyst [28,29] we were able to activate H 2 O 2 and the integrated catalyst, co-catalyst and oxidant functioned as a very efficient peroxidic epoxidation system. Inspired by this result, we reported some other peroxo complexes, which showed higher to much higher catalytic efficiencies [6][7][8][9][10] for olefin epoxidation. In this paper, we report the synthesis, structural characterization, and catalytic epoxidation activities of two oxodiperoxo complexes, [MoO(O 2 ) 2 (PyCOXH) (H 2 O)] (1) (PyCOXH = Pyridine-2-carboxaldoxime) and PMePh 3 [MoO(O 2 ) 2 (PyCO)] (2) (PyCOH = Pyridine-2-carboxylic acid).…”
Section: Introductionmentioning
confidence: 69%
“…accommodates the bidentate ligands by forming oxomonoperoxo complexes of the type [MO(O 2 )(bidentate) 2 ] (the bold font indicates bulky ligand) [6][7][8]. Recently, it has been shown that the MoO(O 2 ) 2 cores with bidentate ligands are useful catalysts in the epoxidation of olefins [6][7][8][9][10]. Epoxidation of olefins and arenes is an important transformation in organic synthesis since the epoxy compounds are widely used, for example in the manufacture of polyurethanes, unsaturated resins, glycols, surfactants, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of NaHCO 3 to the reaction mixture activated the catalytic oxidation process efficiently and gave mainly styrene oxide along with small amount of un-identified product; Scheme 3. Such NaHCO 3 assisted oxidation of styrene has been reported in the literature [31][32][33][34]43].…”
Section: H and 13 C Nmr Studiesmentioning
confidence: 92%
“…It has been found that NaHCO 3 improves catalytic efficiency for the oxidation of organic compounds in presence of H 2 O 2 as terminal oxidant [31][32][33][34]. The corresponding non polymer-grafted molybdenum complex has also been prepared which helped in proposing suitable reaction mechanism and comparing its catalytic performance.…”
Section: Introductionmentioning
confidence: 97%
“…It is cheap, readily available and gives water as the only by-product [15]. Molybdenum and tungsten complexes have been widely investigated because of their demonstrated high activity for selective oxidation with TBHP [16][17][18][19][20] and H 2 O 2 [21][22][23][24][25][26][27][28]. However, to the best of our knowledge, the catalytic performance of Mo(II) and W(II) carbonyl compounds in olefin epoxidation using H 2 O 2 has never been reported.…”
Section: Introductionmentioning
confidence: 99%